(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: To describe some epidemiological features of intentional injury in secondary school students in Ha Noi. Subjects and methodology: A cross-sectional study was conducted on 1.118 students at two secondary schools in Hanoi in 2016. Results: Factors affecting intentional injury included demographic features, emotional disorder, behavioral disorder, peer relationship, drug use, bullying and being bullied, and so on. Conclusion: Intentional injury in secondary school studentsise is affected by demographic features, some psychological disorders, drug use, bullying, and being bullied.